Trojan Horses: A Secret Route for Nanomedicines - Amin, Zoya; Nadeem, Daniya; Shakil, Huzaifa; Jatoi, Munsif Ali; Baloch, Rabail; Ali, Raahim (Current Pharmaceutical Biotechnology, 2025)
The nanoparticles are widely used in various drug delivery applications due to their versatility to encapsulate, cargo loading, and transport of therapeutic agents. Numerous studies have explored the use of nanomedicine-based drug delivery systems for treating various diseases. This research provides a smart and precise review of one of the nanoparticles-based drug delivery approaches, i.e., the Trojan horse strategy which is employed for delivering the drug to the target efficiently and reliably. Furthermore, the applicability of nanomedicines to cancer treatment is discussed, with examples drawn from various systematic studies. The use of different nanomedicine platforms such as liposomes, nanoparticles, spherical nucleic acids, extracellular vesicles, and immune cells acting as Trojan horses is also explored in the context of cancer therapy. Finally, a precise conclusion and future recommendations are provided for future researchers in the field of applied nanotechnology for the pharmaceutical domain.
Keywords: nanotechnology